Adherence to Taking ARV Drugs in Adolescents with HIV/AIDS - Nuraidah, Nuraidah; Wanda, Dessie (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Adherence on taking ARV drugs in adolescents is the main issue in the success of ARV treatment. ARV treatment is related to improving the quality of life in adolescents infected with HIV. Aim: To summarize the factors improving adherence on HIV medication using ARV drugs in adolescents. Method: This article is a review of journal articles related to adherence on taking ARV drugs. Article reviewed were the articles on the past five years, 2015-2019, with a search strategy involving the articles from the following database including Science Direct, Scopus and ProQuest databases. Results: 12 articles related to adherence on ARV medication in adolescents. Conclusion: adherence is a significant aspect that must be maintained in order to overcome the impact of non-compliance on ARV medication as it can affect the quality of life of adolescents with HIV / AIDS.